Micro Hydro Power Plant Design in Ibu Village, West Halmahera In Realizing an Autonomous Energy Village - Muh Muzni Herbelubun; Sherly Asriany; Nam Rumkel (ICETIA, 2016)
Energy is one of the main needs ofhuman life. Energy enhancement can be anindicator of the increasing prosperity of an area, butsimultaneously it also poses problems with supply.An adequate and cheap as well as environmentallyfriendly electrical energy supply for sustainableeconomic and social development. Limitations ofelectrical energy are one of the obstacles in theconstruction and development of ruralcommunities.The micro-hydro power plantis selected as oneof the alternative energy that are environmentallyfriendly, pollution-free, renewable (renewable), notconsumptive of water use, durable (long life), andsmall operational cost is suitable for remote areas.The potential of hydro energy in the Province ofNorth Maluku contained in several regions,including in Ibu Village, West Halmahera. Hydropower potential has been exploited is still relativelysmall. The utilization of hydropower proficiencylevel is still relatively small because the potential isusually located in remote areas that electricitydemand is relatively small, so for micro hydropotential are located far from consumers has notbeen utilized.